2021
DOI: 10.2217/fon-2021-0262
|View full text |Cite
|
Sign up to set email alerts
|

Venetoclax-Based Combinations for the Treatment of Newly Diagnosed Acute Myeloid Leukemia

Abstract: Elderly and/or unfit patients with acute myeloid leukemia have historically been challenging to manage as they were ineligible for what was considered standard of care treatment with induction chemotherapy. The emergence of venetoclax with hypomethylating agents or low-dose cytarabine has substantially improved outcomes in the frontline setting with manageable toxicity. However, this regimen can be challenging to deliver given its differences from standard intensive chemotherapy. In this review, we summarize t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 84 publications
1
15
0
Order By: Relevance
“…The greatest challenge in the field of AML therapy is achieving deep CRs and longterm leukemia-free survival in R/R AML patients [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Despite the fact that we have…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The greatest challenge in the field of AML therapy is achieving deep CRs and longterm leukemia-free survival in R/R AML patients [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Despite the fact that we have…”
Section: Discussionmentioning
confidence: 99%
“…The greatest challenge in the field of AML therapy is achieving deep CRs and longterm leukemia-free survival in R/R AML patients [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Despite the fact that we have gained new insights and a better understanding of cell-intrinsic drivers of AML and new drugs have been developed for targeting select somatic mutations, the majority of R/R AML patients die of leukemia [8][9][10][11][12][13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Final results of the clinical trial are still awaited; however, the authors suggest that this approach could be an alternative to aggressive chemotherapy for obtaining CR prior to allogenic hematopoietic stem cell transplant [127]. A recent approval of a combination of Decitabine with BCL2 inhibitor Venetoclax, which is also directed to AML patients who are not eligible for intensive chemotherapy, diminishes the attractivity of this novel combinatorial approach of Ruxolitinib and Decitabine [127,129]. In particular, preclinical studies have shown promising results upon combining Venetoclax with Ruxolitinib.…”
Section: Jak Inhibitorsmentioning
confidence: 99%